Pengaruh Persepsi Harga, Kualitas Pelayanan, Cita Rasa Terhadap Kepuasan Konsumen Restoran Pawon Sangit Colomadu Karanganyar - Ghanim Permana Putra; Adcharina Pratiwi (Master Manajemen, 2024)
This research was conducted with the aim of analyzing the factors of price perception, service quality, taste on consumer satisfaction at the Pawon Sangit Colomadu Karanganyar Restaurant. This research uses quantitative research types. The data source used is data acquisition in the form of primary data. The population in this study were all customers who had consumed food from the Pawon Sangit Colomadu Karanganyar Restaurant, so the sampling technique was purposive sampling and a sample of 100 respondents was determined. The data analysis techniques used in this research are descriptive analysis, multiple linear regression analysis, t test, f test and coefficient of determination. The results of this research show that the t test, the price perception variable has no significant effect on consumer satisfaction at Pawon Sangit Colomadu Karanganyar Restaurant with a significance value of 0.473 > 0.05, so H0 is accepted, service quality has a significant effect on consumer satisfaction at Pawon Sangit Colomadu Karanganyar Restaurant with a significance value 0.000 < 0.05, then H0 is rejected and Ha is accepted, taste has a significant effect on consumer satisfaction at the Pawon Sangit Colomadu Karanganyar Restaurant with a significance value of 0.006 < 0.05, so H0 is rejected and Ha is accepte.